To tape or not to tape: annular ligament (pulley) injuries in rock climbers—a systematic review - Larsson, R.; Nordeman, L.; Blomdahl, C. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Popularity of rock climbing is steadily increasing. With its inclusion in the Olympic Games this will likely continue. Injuries from rock climbing are also increasing. The most common injury is to the flexor pulley system, consisting of the finger flexors and five annular ligaments (pulleys). Treatment of this injury includes taping of affected fingers, but evaluation of this treatment was previously lacking. The aim of this review was therefore to assess whether taping is associated with better outcomes than non-taping. A secondary aim was to present treatment recommendations or areas for future research.